2016
DOI: 10.3233/jad-151124
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Liposomal Nanoparticle for the Imaging of Amyloid Plaque by Magnetic Resonance Imaging

Abstract: Amyloid binding molecules with greater hydrophilicity than existing ligands were synthesized. The lead candidate ET6-21 bound amyloid fibrils, and amyloid deposits in dog brain and human brain tissue ex vivo. The ligand was used to prepare novel amyloid-targeted liposomal nanoparticles. The preparation was tested in the Tg2576 and TetO/APP mouse models of amyloid deposition. Gd chelates and Indocyanine green were included in the particles for visualization by MRI and near-infrared microscopy. Upon intravenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 29 publications
1
28
0
1
Order By: Relevance
“…There are many visualization procedures exist for imaging of nanoliposomes, For instance to detect particles bigger than 290 nm and impurity with larger particles, a phase contrast optical microscope is an appropriate choice (Gaidukevich et al 2016) and a polarizing microscope is suitable for revealing lamellarity of liposomes (Tanifum et al 2016). Scanning electron microscopy, freeze-fracture, and negative staining are common techniques applied to characterize nanoliposome structures.…”
Section: Visualization Techniquesmentioning
confidence: 99%
“…There are many visualization procedures exist for imaging of nanoliposomes, For instance to detect particles bigger than 290 nm and impurity with larger particles, a phase contrast optical microscope is an appropriate choice (Gaidukevich et al 2016) and a polarizing microscope is suitable for revealing lamellarity of liposomes (Tanifum et al 2016). Scanning electron microscopy, freeze-fracture, and negative staining are common techniques applied to characterize nanoliposome structures.…”
Section: Visualization Techniquesmentioning
confidence: 99%
“…They showed that the synthesized NPs were biocompatible and biologically active with the potential of being used for early detection of AD ( Yin et al, 2015 ). Similarly, in another study, Tanifum et al (2016) reported the synthesis of amyloid fibril-binding ligand ET6-21. The ligand was used to prepare amyloid-targeted liposomes, tagged with Gd chelates and indocyanine green for visualization by magnetic resonance imaging (MRI) and infrared microscopy, respectively.…”
Section: Introductionmentioning
confidence: 78%
“…Working with Jason Eriksen, a neuroscientist at the University of Houston, the team has shown that, in mice, the nanoparticle -which contains a contrast dye used for diagnosing tumours of the brain and spinal cord -can cross the blood-brain barrier to reach the brain, where it binds to amyloid-β deposits (pictured, green) and emits a signal when scanned using the low-field strength MRI machines that are commonly found in clinics 8 .…”
Section: Elie Dolgin Is a Science Writer In Somerville Massachusettsmentioning
confidence: 99%